An experimental study on the influence of low - cement content on improved filling characteristics of geotextile bags filled with fine tailings slurry - Li, Hui; Shi, Miao; Zhang, Jia; Peng, Liangliang (Frontiers in Materials, 2025)
Constructing dams with geotextile bags filled with fine tailings can overcome the shortage of sand and gravel resources for dam construction. In addition, it can also prevent safety hazards caused by the deposition of fine tailings in tailings reservoirs. However, the geotextile bags were made of polypropylene woven fabrics, whose surface pore size can influence both the dehydration rate and the amount of tailings consolidated in geotextile bags. To optimize the construction efficiency of geotextile bag dams and improve the utilization rate of fine tailings, geotextile bags filling experiments, X-ray diffraction experiments and scanning electron microscopy experiments were performed by revealing the influence mechanism of low-cement content on the filling characteristics of geotextile bags from macro and micro perspective. The results showed that the addition of low-content cement as a curing agent effectively solved the contradiction between the permeability and the utilization rate of fine tailings. Compared with the fine tailings slurry without cement addition, when 1%, 3%, and 5% cement was added, the drainage efficiency increased by 12.90%, 23.39%, and 49.6% respectively; the sand retention ratio improved by 0.25%, 10.44%, and 13.62% respectively. Calcium silicate hydrate (C-S-H) calcium silicoaluminate hydrate (C-A-S-H), calcium carbonate, and calcium aluminate (CH) were found in the consolidated tailings. The hydration of cement within the geotextile bags formed a hydrated membrane layer that wrapped, adsorbed, and encapsulated fine tailings particles, accumulating on the surface of coarse tailings to create a composite particle structure. With the increase of cement content, the amount of hydration products mentioned above increased accordingly, and their diffraction peaks gradually enhanced, which not only contributed to effectively alleviate the surface blockage of geotextile bags but also improve the filling degree of geotextile bags, and thus increasing the effective normal stress transmitted to the contact surface of laminated geotextile bag in dam construction. Considering construction efficiency, the utilization rate of fine tailings, and construction cost, the optimal cement content was determined to be 3%. This research is expected to offer insightful and transferable experiences for dredging projects, coastline governance, soft foundation strengthening, among other applications.